Some Issues in Treating the Changes of Circumstances under English Law - Juhász, Ágnes (Pro Futuro, 2020)
A szerződéskötést követően a körülményekben bekövetkező lényeges változások figyelembe vételére és kezelésére valamennyi jogrendszeren belül kialakultak álláspontok. A különböző jogintézmények, alkalmazott megoldások bár sok szempontból hasonlatosak, azonban számos eltérés is megfigyelhető. A tanulmány átfogóan mutatja be, hogy az angol jog miként kezeli a körülménybeli változásokat és azok szerződésekre kifejtett hatását. Ennek során bemutatásra kerül a szerződés meghiúsulásának tana (frustration of contract) és az elmélet kialakulásának alapjául szolgáló, bírósági esetjog. All legal systems have their own solution for the treatment of the essential change of circumstance subsequent to the conclusion of the contract. Some of them allow for the judicial amendment of the contract, if the conditions of the clausula rebus sic stantibus are fulfilled. There are other states, where the possibility to modify the contract by judicial act in case of an essential change of circumstances subsequent to the contract conclusion has only recently been recognised by the national legislation. In the following, it is to be reviewed how and by what means and models English law treats those changes of circumstances which occur after the conclusion of the contract and significantly reshape the contractual relationships.